Inheritance of shortday induced dwarfing in photesensitive cowpeas - Ishiyaku, M.; Singh, B. (African Journals Online, 2001)
Cowpea [ Vigna unguiculata (L.) Walp.] is an important source of food and fodder in the dry savanna of West Africa. Traditional cowpea varieties are photosensitive (PS), growing profusely when planted in long days and they flower when days become shorter. However, we have observed that all PS cowpea varieties exhibit dwarf characteristics when planted during short-days. This study was undertaken to confirm this observation and to elucidate the inheritance of shortday induced dwarfing in PS cowpea. Two PS and two Photoinsensitive (PI) cowpea varieties were evaluated at IITA Kano Station, Nigeria (12003'N latitude and 8032'E longitude) at 4 planting dates. As expected, PS varieties flowered earlier when planted during short days (<12.5 h., February and October plantings) and later during long days (>13 h., May and July plantings). However, they became extremely dwarf during short days due to lack of internode elongation resulting in a rosette appearance. The mean plant heights of PS varieties were 20.5 cm, 142 cm, 89.0 cm and 15.0 cm, when planted in February, May, July and October, respectively. The corresponding plant heights of the PI varieties were 39.0 cm, 31.5 cm, 26.0 cm and 24.5 cm. The parental, F1, F2 and backcross populations derived from a PI variety IT87D-941-1 and a PS variety, Kanannado were evaluated in short day conditions and selected F3 progenies tested in long-day conditions. The genetic segregation revealed that short-day-induced dwarfing of PS is controlled by a single recessive gene pair which is designated as 'psps (photosensitive). The complete correspondence between dwarfing under short-day conditions and PS for flowering, indicates that both phenomena are manifestation of the same PS gene pair.